Localized proton magnetic resonance spectroscopy of the cerebellum in detoxifying alcoholics - Seitz, Dietmar; Widmann, Uwe; Seeger, Uwe; Nägele, Thomas; Klose, Uwe; Mann, Karl; Grodd, Wolfgang (Alcoholism, 2006)
An increased daily alcohol consumption results in neurological symptoms and morphological central nervous system changes, e.g. shrinkage of the frontal lobes and the cerebellar vermis. Brain shrink-age can be due to neuronal loss, gliosis, or alterations of (cell) membrane constitutes/myelin. Neuronal, glial, and metabolic change can be measured in vivo with proton magnetic resonance spectroscopy. A total of 11 alcoholics and 10 age-matched volunteers were examined by magnetic resonance imaging and localized magnetic resonance spectroscopy at an echo time of 135 and 5 msec. Pea integral values were calculated for N-acetylaspartate (NAA), choline (Cho), myo-inositol (ml), glutamate/glutamine (Glx), and normalize to phosphocreatine/creatine (Cr). Patients had a significant shrink-age of the cerebellar vermis. NAA/Cr and Cho/Cr ratios were r duced in both sequences, but the NAA/Cr reduction was only significant in long echo time, although the Cho/Cr reduction WAS significant in short echo time. The ml/Cr and Glx/Cr ratios did not show any significant difference between volunteers and patients. The decrease of NAA/Cr in alcohol dependent patients is consistent with neuronal loss. The Cho/Cr decrease and an unchanged ml/C may reflect cell membrane modification or myelin alterations alcohol-dependent patients. These changes lead to brain shrinkage although hydration effects and gliosis are less likely.